LYMPH NODE CYTOLOGY REPORTING BY “SYDNEY SYSTEM: A COMPREHENSIVE APPROACH TO LYMPH NODE FINE-NEEDLE ASPIRATION CYTOLOGY” - ABHISHEK SINGH; SHIVENDRA DUTT SHUKLA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The major goal of the current investigation was to categorize the lesions found in lymph nodes using the Sydney approach for reporting cytopathology of lymph nodes. Methods: This investigation was carried out retrospectively at Maharshi Vishwamitra autonomous state medical college in Ghazipur, between January 2022 and December 2023. Total 250 patients were examined; cytopathologically assessed, and categorized using the Sydney method. Whenever feasible, a link between histopathology and clinical findings was made. Results: Out of 250 cases, 04% (n=10) were inadequate/non-diagnostic (L1 category), 87% (n=218) were benign (L2 category), 02% (n=05) were atypical (L3 category), 2.8% (n=2.8%) were suspicious of malignancy (L4 category), and 04% (n=10) were malignant (L5 category). The sensitivity and specificity was 94.4% and 98.1%. The positive predictive value, negative predictive value, and diagnostic accuracy were 94.4%, 98.1%, and 97.1%, respectively. For L2 category, the probability of malignancy was 1.9 %, for L3 category 66.6% and for L4 and L5 was 100%. Conclusion: The suggested reporting system intends to provide consistent recommendations on management regimens, improve communication between cytopathologists and doctors, and standardize reporting.